2011
DOI: 10.1002/alr.20068
|View full text |Cite
|
Sign up to set email alerts
|

The impact of osteitis on disease severity measures and quality of life outcomes in chronic rhinosinusitis

Abstract: BACKGROUND The significance of osteitis in the management of recalcitrant chronic rhinosinusitis (CRS) has yet to be clearly understood and clinical outcomes data for these patients is lacking. Osteitis has been characterized by inflammatory infiltrate, osteoneogenesis, and bony sclerosis with remodeling. In this study we sought to determine if osteitis negatively impacts quality-of-life (QOL) or clinical outcomes following endoscopic sinus surgery (ESS). METHODS 190 adult patients with CRS were prospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 17 publications
4
81
1
3
Order By: Relevance
“…Saylam et al 400 showed markedly worse subjective scores for patients with osteitis (as determined by higher SPECT scan) compared to a non-osteitis cohort. Bhandarkar et al 78 found no difference on Rhinosinusitis Outcome Measure (RSOM), RSDI, or CSS in patients with and without osteitis. Nonetheless, fewer patients with osteitis achieved improvement from ESS after controlling for baseline diseasespecific factors.…”
Section: S55mentioning
confidence: 99%
See 1 more Smart Citation
“…Saylam et al 400 showed markedly worse subjective scores for patients with osteitis (as determined by higher SPECT scan) compared to a non-osteitis cohort. Bhandarkar et al 78 found no difference on Rhinosinusitis Outcome Measure (RSOM), RSDI, or CSS in patients with and without osteitis. Nonetheless, fewer patients with osteitis achieved improvement from ESS after controlling for baseline diseasespecific factors.…”
Section: S55mentioning
confidence: 99%
“…CT scans do provide important information on anatomy, location of disease, extent of disease, and presence of osteoneogenesis. Some have tried to identify predictive data from CT scans, and have noted that presence of osteoneogenesis on CT is associated with diminished QoL gains after surgery, 78 and also that intrasinus quantity and density of opacification may correlate with QoL measures. 79 Although both endoscopic and radiographic measures may be further refined in the future to better correlate with QoL measures and outcomes, it seems clear that they are not measuring exactly the same constructs, and failure to identify a high level of correlation with symptoms does not imply that the measure is not useful.…”
Section: Ivc Measurement Of Disease Severitymentioning
confidence: 99%
“…The effect of ESS on improving olfactory dysfunction has remained controversial due to lack of comprehensive evidence. Range of improvement has been reported from 25% to100% according to some prior studies; while others have reported no improvement or even reduced olfactory function following ESS [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 94%
“…This could explain the recurrence of the mucosal disease after surgical treatment and may indicate that these osteitic lesions act as the source of the chronic inflammation with worse baseline measures of disease severity and inflammation [3][4][5][6][7]. Other investigators found that the incidence of osteitis reaches 64% in patients with recalcitrant CRS [8].…”
Section: Opinionmentioning
confidence: 99%